2016
DOI: 10.1016/j.cobeha.2016.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Reward, learning and games

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. AbstractThe link between reward and learning has chiefly been studied scientifically in the context of reinforcement learning. This type of learning, which relies upon midbrain dopaminergic response, differs greatly from the learning valued by educators, which typically involves declarative memory formation. However, with recent insights regarding the modulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 81 publications
0
23
0
Order By: Relevance
“…We therefore suggest that gamers/learners’ frequent in-game interaction may strengthen or increase their FC associated with language processing. Additionally, in view of the reward effect on gamers’ motivation to interact in FL/L2 ( Peterson, 2012 ; Howard-Jones and Jay, 2016 ), we further posit that brain reward circuit may play a moderating role in the increased FC within gamers’ brain network.…”
Section: Possible Neural Mechanism Underlying Mmorpgs’ Educational Romentioning
confidence: 89%
See 1 more Smart Citation
“…We therefore suggest that gamers/learners’ frequent in-game interaction may strengthen or increase their FC associated with language processing. Additionally, in view of the reward effect on gamers’ motivation to interact in FL/L2 ( Peterson, 2012 ; Howard-Jones and Jay, 2016 ), we further posit that brain reward circuit may play a moderating role in the increased FC within gamers’ brain network.…”
Section: Possible Neural Mechanism Underlying Mmorpgs’ Educational Romentioning
confidence: 89%
“…However, the underlying behavioral and neural mechanisms of MMORPG-based FL/L2 development remain unexplored. Because learners/gamers are more motivated to interact with peers in MMORPGs’ contexts than they are in traditional teaching settings ( Peterson, 2011 , 2012 ; Bytheway, 2014 ; Shahriarpour and Kafi, 2014 ; Zheng et al, 2015 ; Howard-Jones and Jay, 2016 ), to figure out the source of such stronger motivation appears to be fundamental for investigating the behavioral and neural mechanisms under discussion. Evidence has shown that rewarding the gamers for meeting progressively demanding performance levels increased gamers’ intrinsic motivation ( Cameron et al, 2001 ; Pierce et al, 2003 ).…”
Section: Mmorpgs’ Benefit For Gamers’/learners’ Fl/l2 Learningmentioning
confidence: 99%
“…As declarative learning plays a predominant part in education, these results stress the need for a better understanding of the role that reward (and its prediction) plays in declarative learning. Despite an early reluctance of educational theorists toward incorporating reward in educational settings, its role has been reconsidered in recent years [ 35 ]. One potential illustration is the testing effect [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The value of reward in education has been controversial. In fact, while some educational programs emphasize the value of reward systems (e.g., badges; see also Howard-Jones and Jay 2016;O'Byrne et al 2015), some other researchers argue against any form of rewards or incentive systems in education (e.g., Kohn 1993). An important phenomenon to discuss, relating to the role of reward in education, is the undermining effect (Deci 1971).…”
Section: Implications For Educationmentioning
confidence: 99%